Detection of Lead in Some Soft White Cheeses Manufactured in The Syrian Coast - سلطانه علي (Latakia University Journal -Biological Sciences Series, 2021)
The research aims to detect the concentration of lead in some soft white cheeses (Akkawi, Baladiyeh, Meshallaleh, Mousnarna, Shanklish) manufactured in various regions of the Syrian coast (Lattakia, Jableh, Baniyas, Tartous). Results showed that the solid substance is in conformity with the Syrian specifications for soft white cheeses, which the lowest value was recorded in the local cheese 41.75% and the highest value was in the mashalal cheese 53.63%. The concentration of lead was estimated as the follwing 0.061 , 0.063 ,0.098 , 0.093 and 0.185mg/kg in each of Akkawi, Baladiah, AMashlala, Musannarah and Shanklish, respectively. The cheeses produced in the region of Banias recorded the highest values of lead concentrations compared to the other studied regions, where the highest value was recorded in Shanklish 0.572 mg/kg, while the cheeses manufactured in Jableh were the lowest contaminated, where the lowest value was recorded in Baladi cheese with an average of 0.044 mg/kg. Results showed that all values ​​of the daily intake resulting from the consumption of 100 g of the studied cheeses are less than 0.0241 mg/kg which is the provisional tolerable daily intake (PTDI) of lead resulting from the consumption of cheese.